(untitled) (Analele Universității din București. Științe Politice, 2025)
Hungarian-Romanian relations are difficult to assess because they involve a vast set of actors: from diplomats to civil society, from political parties to churches. If convergence in foreign policy is to be achieved and if genuine reconciliation is to take place, all these actors have to be taken into consideration and have to engage in a concerted manner. Bilateral relations between Hungary and Romania benefit from a dense network of cooperation initiatives, but they are neither sustainable, nor integrated into a vision aiming for convergence and reconciliation. Political will, joint historical research projects and youth bi-ethnic socialization are critical in creating a bilateral relation supported by true reconciliation.